Influence of Emulsifier on Surface Mass Transfer Based on Molecular Dynamics Simulations - Kong, Lingyun; Luo, Wanli; Feng, Biao; Quan, Xiujie (Frontiers in Materials, 2020)
To explore the effect of emulsifier structure on mass transfer performance, and provide theoretical basis and ideas for the structure design of new asphalt emulsifier. The mass transfer process of the anionic surfactant sodium dodecyl benzene sulfonate (SDBS) and its four isomers on the solid surface of calcium carbonate, as well as the resulting main chemical component of its aggregates, were studied using molecular dynamics (MD) simulations. It was found that the SDBS and its isomers can be adsorbed on the calcium carbonate surface over a relatively short time and gradually form an aggregate structure during the mass transfer process. In this process, Na ions have no obvious aggregation behavior in the polar head of the emulsifier. The calculated interfacial interaction energy indicates that the adsorption performance and aggregation on the calcium carbonate surface are related to the degree of branching and steric hindrance of the emulsifier molecule. Both the lipophilic group and the hydrophilic group in the emulsifier promote its diffusion into the solution. The results show that molecular dynamics（MD） simulations can be used to supplement experiments to provide the necessary microscopic information and theoretical basis for further experimentation.